Physical Activity Among Predominantly White Middle-Aged and Older US Adults During the SARS-CoV-2 Pandemic: Results From a National Longitudinal Survey - Joseph, Rodney P.; Pituch, Keenan A.; Guest, M. Aaron; Maxfield, Molly; Peckham, Allie; Coon, David W.; Kim, Wonsun; Langer, Shelby L. (Frontiers in Public Health, 2021)
Background. The first COVID-19 case in the US was diagnosed late January 2020. In the subsequent months, cases grew exponentially. By March 2020, SARS-CoV-2 (the novel coronavirus that causes COVID-19) was a global pandemic and the US declared a national emergency. To mitigate transmission, federal guidelines were established for social and physical distancing. These events disrupted daily routines of individuals around the world, including Americans. The impact of the pandemic on PA patterns of Americans is largely unknown, especially among those at greater risk for severe COVID-19 outcomes. The aim of this study was to assess levels of PA over time during the pandemic among US adults aged > 50 years. Methods. Data were collected as part of a web-based, longitudinal, 3-wave study examining health and well-being among adults aged > 50. PA data were collected at Waves 2 and 3 using the International Physical Activity Questionnaire-Short Form (IPAQ-SF). At Wave 2 (conducted mid-May to early June, 2020), participants completed the IPAQ-SF twice, once in reference to a typical 7-day period before the pandemic, and again in reference to the past 7 days. At Wave 3 (conducted mid-June to early July 2020), participants completed the IPAQ-SF once, with reference to the past 7 days. Potential predictors of PA change included: pre-pandemic PA levels, perceived COVID-19 threat, self-rated general health, and number of chronic disease conditions. Results. Respondents (N=589) had a mean age of 63 ± 7.39 years and were mostly female (88%) and non-Hispanic White (96%). Mean MET-minutes/week across the three time-referents were 2904 (pre-pandemic), 1682 (Wave 2 past 7-days), and 2001 (Wave 3 past 7-days), with PA declining between the first and second time referents (d = -.45, p < .001) and remaining below pre-pandemic levels at the third (d = -.34, p < .001). Changes over time were predicted by pre-pandemic PA and self-rated general health (p’s < .05). Conclusions. Effective strategies are needed to promote safe and socially-distanced PA among adults aged > 50 years until the risk of contracting COVID-19 subsides. In the post-pandemic era, PA programming will be imperative to address pandemic-associated declines in PA.